Corrosion Behavior of Titanium in the Presence of Some Drugs Based on Amino Groups - Jassim, Rasha A.; Ayal, Asmaa Kadim; Sando, Muna S.; Farhan, Ahlam Mohammed; Khammas, Sameaa J. (Iraqi Journal of Science, 2024)
This study evaluated the effect of two different types of amino group-containing pharmacological inhibitors on titanium corrosion under acidic conditions. The first inhibitor examined was the antibiotic trimethoprim. The second inhibitor studied was the nonsteroidal anti-inflammatory drug voltaren. The results showed that titanium had a high corrosion current in the absence of a corrosion inhibitor, however, trimethoprim notably enhanced corrosion resistance and protection percentages of titanium (%IE) at higher concentrations by adhering to the metal surface, as evidenced by improved protection percentages. Furthermore, the results showed that as Voltaren concentration was increased, both corrosion resistance and inhibition efficiency decreased. This demonstrates that less Voltaren was absorbed onto the metal surface as compared to trimethoprim.